The Effect of Dhuha Prayer and Istighosah on The Religious Character of Tsanawiyah Madrasah Students - Iskandar Yusuf; Umar Fauzan; Noor Malihah (Nazhruna: Jurnal Pendidikan Islam, 2022)
The purpose of this article is to find out how influential the dhuha prayer and istigasah prayer activities are in developing the religious character of students at MTs Daruttaqwa Gresik. In this study, researchers used descriptive quantitative methods. Data collection techniques used are interviews, questionnaires/questionnaires, and documentation. The conclusion of this research is that the effect of dhuha prayer and istigasah activities on the religious character of students can be seen through multiple regression tests with the results of R count > R table, it can be concluded that the duha prayer and istigasah activities have an influence on the religious character of students at MTs The Noor Pacet Mojokerto.